The role of mitochondrial fission in intervertebral disc degeneration. Issue 2 (February 2023) - Lin, Z.; Wang, H.; Song, J.; Xu, G.; Lu, F.; Ma, X.; Xia, X.; Jiang, J.; Zou, F.
Summary: Low back pain (LBP) is an extremely common disorder and is a major cause of disability globally. Intervertebral disc degeneration (IVDD) is the main contributor to LBP. Nevertheless, the specific mechanisms underlying the pathogenesis of IVDD remain unclear. Mitochondria are highly dynamic organelles that continuously undergo fusion and fission, known as mitochondrial dynamics. Accumulating evidence has revealed that aberrantly activated mitochondrial fission leads to mitochondrial fragmentation and dysfunction, which are involved in the development and progression of IVDD. To date, research into mitochondrial dynamics in IVDD is at an early stage. The present narrative review aims to summarize the most recent findings about the role of mitochondrial fission in the pathogenesis of IVDD.